Indecent Dressing among Female Undergraduate Students: Impact on Emotional Adjustment and Cognitive Engagement of Their Male Counterparts in Anambra State - Elizabeth Ifeoma Anierobi; Ogochukwu Gloria Nnonyelu; Patricia Ego Nwaru (Scientia Publica Media, 2025)
This study sought to x-ray indecent dressing among female undergraduates in a university community and its impact on the emotional adjustment and cognitive engagement of their male counterparts in Anambra State. The descriptive design was adopted for this study and guided by three research questions. The sample size for the study was 542 undergraduate male students in a government-owned university in Anambra State drawn through a multi-stage sampling procedure. Researcher designed questionnaire validated by experts in the field of Education was used in eliciting responses from the respondents. The reliability of the instrument was determined using Cronbach’s alpha to estimate the internal consistency of the instrument. The analysis gave an alpha coefficient of 0.71, 0.73, 0.70 and 0.72 for clusters 1 to 4 respectively and 0.71 for the whole cluster. Data collected were analyzed using descriptive statistics. Findings of the study revealed prevalence of indecent dressing among female undergraduate students in Anambra State. It also showed that indecent dressing among female students are sustained by many factors such as imitation of western dressing style, peer/social group pressure, fashion in vogue and poor parenting. The result further revealed that curbing indecent dressing in tertiary institutions in Anambra State is possible through creating of awareness on proper dress codes for students using bill boards. Finally, the findings of the study showed that indecent dressing among female undergraduate students has a negative impact on both the emotional adjustment and cognitive engagement of their male counterparts in Anambra State. It was recommended among others that there should be enforcement of policies against indecent dressing on campuses.